Women's Education in the Perspective of Al-Qur'an Tarbawi: Orientation, Values, and Relevance in the Modern Era - Hasmi Nur Bayhaqi; Ali Mas'ud (Konsultan Jurnal Ilmiah Indonesia, 2025)
Women's education is one of the important pillars in the development of Islamic civilization, but the gap between the normative principles of the Quran and social reality remains a recurring issue. Although the Quran affirms spiritual and epistemological equality between men and women, educational practices in some Muslim societies are still influenced by cultural biases and patriarchal structures. This article aims to analyze the concept of women's education from a Quranic tarbawi perspective by examining its educational orientation, the tarbawi values that underpin it, and its relevance to the modern context. This research employs a literature study approach, examining verses from the Quran, commentaries, and contemporary academic literature on women's education and the construction of educational values. The study results indicate that women's education from a Quranic perspective has an integral normative framework, encompassing spiritual-moral, intellectual-professional, and social-civilizational dimensions. Educational values such as monotheism, ethics, equality, trust, and empowerment form a conceptual foundation that positions women as agents of change and pillars of civilization. This finding is relevant to the needs of modern education, which demands that women not only be intellectually capable but also possess spiritual resilience and social capacity that are adaptable to digital dynamics and contemporary moral challenges. This article asserts that strengthening women's education based on educational values is a fundamental strategy for building character-driven families, civilized societies, and sustainable Islamic civilization.